The Concept of Qath`i and Zhanni and Its Implication to Religious Behavior among Muslim Communities in Lombok - Bin Mujib, Lalu Supriadi; Hamim, Khairul; Bin Gunardi, Setiyawan (al-'adalah, 2020)
The difference in understanding of the concepts of qath`i and zhanni is the root of the problem that causes conflict among Muslims, especially among the Salafi and non-Salafi communities. This study aims to determine the concepts of qath`i and zhanni, the response of the Salafi and non-Salafi communities to the concepts, and its implications in shaping their religious behavior. This study used a descriptive qualitative approach with a case study method and a field research design. Collecting data using observation, interview, and documentation techniques. The data analysis technique uses the description, interpretation, criticism, and conclusion stages. The results of this study indicate that the concepts of qath`i and zhanni are used by ulama Ushul Fiqh to analyze legal texts from the linguistic aspect that are used as standards for assessing the legality and validity of the law. Salafi and Non-Salafi communities agree on qath`ias an inviolable conception, whereas zhanni is not considered. Methodological differences in identifying the concept of qath`i and zhanni areas have implications for religious behavior among Muslims in Lombok, Mataram. By using a textual approach and ignoring the contextual approach, Salafis consider laws that are still in a clear area as qath`i. On the other hand, Non-Salafis use textual and contextual approaches to conclude that the law that is still being debated is zhanni.